Fun English language learning for Kids - Yuli Choirul Umah (EDUTEC : Journal of Education And Technology, 2019)
Currently, the English language introduction in elementary school, where subjects are not too needed for children, but for the author himself has a different opinion. For English writers need to be introduced to children. The introduction of English for children is certainly in a way that is different from secondary school children, such as JUNIOR and HIGH school. The introduction of English for children with the intent of not burdensome, does not make the child bored, packaged in the form of play while studying, or even the sense of not learning but play that gives them English skills. Singing, games, drawing, coloring, storytelling, and more are effective methods for introducing English to children.